Deux millénaires ou deux siècles de constructions mégalithiques au Sénégal et en Gambie ? Nouvelles dates pour Wanar et révision des contextes archéologiques - Luc Laporte; Jean-Claude Lefèvre; Matar Ndiaye; Christine Oberlin; Adrien Delvoye; Mathilde Stern; Abdoul Kader Faye; Aziz Ballouche; Jean-Paul Cros; Selim Djouad; Laurent Quesnel (Afrique Archéologie Arts, 2022)
The megaliths of Senegal and The Gambia comprise nearly 30,000 erected stones recorded over a surface of around 30,000 km², mainly in the northern basin of the Gambia River. The very first radiocarbon date associated with the megaliths of Senegal and Gambia was published in 1965. Most of the radiocarbon dates obtained since then concern the westernmost part of Senegambian megalithism. More than 28 additional dates for the necropolis of Wanar (Senegal) alone, can now be added to the 25 previously available. Bayesian models incorporating the stratigraphic constraints specific to each sequence for each of the studied monuments, independently of each other, enable us to clarify these data and to propose an historic scenario. They illustrate a regional settlement sequence of more than two millennia, whereas the construction of standing stone circles could not have lasted for more than a few hundred years. Two radiocarbon dates on human teeth confirm that the death of the buried individuals dates from the eleventh or twelfth centuries AD.